Method for effectively improving ammonium storage performance of manganese oxide by soaking manganese oxide in tannic acid solution

The modified P2 sodium manganese oxygen material through tannin acid immersion, the problem of low capacity and poor electrochemical performance of the aqueous ammonium ion battery electrode material is solved, and excellent electrochemical performance and high capacity are achieved.

CN119650678APending Publication Date: 2025-03-18NANJING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411895768.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The electrode materials of aqueous ammonium ion batteries have problems with low capacity and poor electrochemical performance.

Method used

Using tannin acid soaked modified P2 sodium manganese oxygen material as the positive electrode material, an electrode material with excellent electrochemical properties was prepared by calcining sodium carbonate and dimanganese trioxide and soaking tannin acid.

Benefits of technology

A stable electrochemical window of 0-1.2V was achieved in the CV curve at 1.5mVs-1 sweep speed, and a capacity of 196mAh g-1 was reached at a current density of 0.5A g-1, showing good electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HSA0000299892430000011
    Figure HSA0000299892430000011
  • Figure HSA0000299892430000012
    Figure HSA0000299892430000012
  • Figure HSA0000299892430000021
    Figure HSA0000299892430000021
Patent Text Reader

Abstract

The invention discloses an application of a tannic acid soaked manganese oxide in an aqueous ammonium ion battery electrode material, and relates to the technical field of energy storage materials. A part of Mn element in a P-phase sodium manganese oxide compound is dissolved by soaking with tannic acid, so that the change of Mn-O bonds is influenced, the bond length is shortened, the bond energy is enhanced, the material interlayer spacing is increased, more active sites can be exposed, and more NH4 < + > ions can be accommodated for intercalation / deintercalation. An electrochemical test result shows that the P2-phase sodium-manganese-oxygen electrode soaked by the tannic acid can reach the high capacity of 196mAhg <-1 > when storing NH4 < + >, and shows good electrochemical performance. The preparation method disclosed by the invention is high in controllability, simple in preparation process and low in raw material cost, and is expected to become a novel energy storage device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of energy storage materials and relates to the modification of a manganese-based positive electrode material used in aqueous ammonium ion batteries. Background Art

[0002] The development of economical and safe electrochemical energy storage devices is of great significance. In the past few decades, lithium-ion batteries have been widely used in portable electronic products and electric vehicles due to their high energy density and long cycle life, and have achieved commercial success. However, their further development is subject to many limitations, such as the shortage of lithium resources, toxic electrolytes, and flammable and explosive problems. Aqueous rechargeable batteries have attracted widespread attention due to their low cost, good safety, high ionic conductivity, and fast diffusion kinetics.

[0003] Most aqueous batteries use metal ions as charge carriers, such as Li + 、Na + , K + 、Zn 2+ Mg 2+ etc., but non-metallic ammonium ions (NH4 + ) has its unique advantages as a charge carrier. Compared with metal ions, NH4 + It has the characteristics of abundant reserves, low corrosiveness and low hydrogen precipitation, and has a low molar mass (18gmol -1 ) and hydrated ion size, so ammonium ions can diffuse quickly in the electrolyte during charge and discharge. + Energy storage devices that are current carriers will not produce metal dendrites, and therefore will not cause safety issues. It is worth noting that spherical metal ions (such as Li + ) has no preferred orientation, while NH4 + The tetrahedral structure of ammonium ions (NH4 + ) can not only be embedded in the electrode by forming covalent-ionic bonds but also act as reversible redox centers for charge transfer.

[0004] Aqueous ammonium ions have opened up a new direction in the field of energy storage, but due to their large volume radius, they are prone to low capacity and unstable structure, which has a great impact on the performance of electrode materials. Therefore, it is crucial to find unique and suitable electrode materials and carry out in-depth theoretical and applied research on aqueous ammonium ion energy storage devices. Summary of the invention

[0005] The main purpose of the present invention is to provide a method for modifying manganese oxide compounds with excellent electrochemical performance, simple process and low cost for aqueous ammonium ion battery positive electrode materials, so as to solve the problems of low capacity and poor electrochemical performance.

[0006] In order to achieve the above-mentioned purpose of the invention, the purpose of the present invention is achieved through the following technical solutions:

[0007] A P2 sodium manganese oxide material, the preparation method of which comprises the following steps:

[0008] S1. Weigh sodium carbonate and manganese trioxide in a mortar, mix briefly and grind evenly for 30 minutes to obtain a black powder; evenly put the obtained black powder into a corundum porcelain boat, place it in a muffle furnace for calcination, and obtain a P2 phase sodium manganese oxide material.

[0009] S2. Weigh tannic acid and dissolve it in a beaker. Mix well and transfer to a centrifuge tube. Weigh the synthesized P2 phase sodium manganese oxide material and pour it into a centrifuge tube. Mix well and transfer to an oven for heating. Centrifuge and wash with alcohol 3 times to obtain a black solid. Dry the black solid in an oven overnight to obtain the P2 phase sodium manganese oxide material modified by tannic acid soaking.

[0010] Wherein, in step S1, the molar ratio of sodium carbonate to manganese trioxide is 0.5-0.9.

[0011] Preferably, the calcination in step S1 is high-temperature calcination at 500-900° C. for 10-15 hours in a muffle furnace.

[0012] Preferably, the concentration of tannic acid in step S2 is: 0.02-0.08 g tannic acid dissolved in 100 ml water.

[0013] Preferably, the oven heating conditions in step S2 are: heating at 50-100° C. for 10-30 min.

[0014] Application of any of the above-mentioned P2 phase sodium manganese oxide materials as electrode materials in aqueous ammonium ion batteries.

[0015] The above application, the method for preparing an aqueous ammonium ion battery using a P2 phase sodium manganese oxide material as an electrode material comprises the following steps:

[0016] 1. Preparation of working electrode: Mix the P2 sodium manganese oxide material, conductive agent and binder described in any one of the above items in a ratio of 8:1:1, add a small amount of NMP solvent, grind evenly, directly apply it on carbon cloth, and dry it in a vacuum drying oven to obtain a working electrode plate coated with P2 sodium manganese oxide;

[0017] 2. Preparation of aqueous ammonium ion battery: Cut the working electrode carbon cloth coated with P2 phase sodium manganese oxide material, clamp it into the electrode clamp, then screw the working electrode, counter electrode and reference electrode into the beaker device in turn, pour in the electrolyte, tighten it and let it stand to obtain an aqueous ammonium ion battery based on P2 phase sodium manganese oxide electrode material.

[0018] In the above application, in step 1, the binder is PVDF and the conductive agent is Super P.

[0019] In the above application, in step 2, the counter electrode is a platinum sheet, and the reference electrode is a saturated silver chloride electrode.

[0020] In the above application, the electrolyte is ammonium sulfate.

[0021] The beneficial effects of the present invention are:

[0022] 1. The present invention designs an aqueous ammonium ion battery based on a P2 phase sodium manganese oxide electrode material soaked in tannic acid. It has the following advantages: the synthesis method of the P2 phase sodium manganese material is simple, low cost, low production difficulty, and environmentally friendly; secondly, the electrolyte is an aqueous solution, which is non-toxic, highly safe, low-cost, pollution-free, and easy to mass produce.

[0023] 2. The present invention provides an aqueous ammonium ion battery based on P2 phase sodium manganese oxide electrode material with excellent electrochemical performance at 1.5 mVs -1 The CV curves at the scan rate showed a stable electrochemical window of 0-1.2 V. -1 At a current density of 1.5 %, the capacity can reach 196 mAh g -1 . BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is an EDS graph of the P2 sodium manganese oxide material electrode material A prepared in Example 1 of the present invention and the P2 sodium manganese oxide electrode material B after being soaked in tannic acid.

[0025] Figure 2 1 and 2 are XRD diagrams of electrode material A, Example 1B, Example 2B, and Example 3B prepared in the present invention.

[0026] Figure 3 3B are Laman diagrams of electrode material A, Example 1B, Example 2B, and Example 3B prepared by the present invention.

[0027] Figure 4 The electrode materials A, Example 1B, Example 2B and Example 3B prepared by the present invention are used in aqueous ammonium ion batteries at 1.5 mVs -1 Cyclic voltammetry curves at different scan rates.

[0028] Figure 5 The electrode materials A, Example 1B, Example 2B and Example 3B prepared by the present invention are used in aqueous ammonium ion batteries at 0.5A g -1 Capacity comparison chart at current density.

[0029] Figure 6 It is a rate comparison diagram of electrode material A, Example 1B, Example 2B, and Example 3B prepared by the present invention for aqueous ammonium ion batteries at different current densities. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0031] The sodium carbonate, manganese trioxide, tannic acid and ammonium sulfate used in the embodiments of the present invention are commercially available analytically pure reagents.

[0032] The water used in the embodiment of the present invention is deionized water, and the ethanol used is anhydrous ethanol.

[0033] In the embodiment of the present invention, each time the ethanol is used for washing, the material is immersed in ethanol and then centrifuged.

[0034] Example 1

[0035] (I) P2 sodium manganese oxide material, the preparation method is as follows:

[0036] Weigh 0.74193g of sodium carbonate and 1.5787g of manganese trioxide in a mortar, mix them evenly and grind them for 30 minutes to obtain a black powder; evenly put the obtained black powder into a corundum porcelain boat, place it in a muffle furnace and calcine it at 900°C for 15h to obtain a P2 phase sodium manganese oxide material A; weigh 0.02g of tannic acid and dissolve it in 100ml of aqueous solution, mix it evenly and transfer it to a centrifuge tube; weigh 0.3g of P2 phase sodium manganese oxide material A and pour it into a centrifuge tube, mix it evenly, transfer it to an oven, 85°C for 15min; centrifuge and wash it with alcohol 3 times to obtain a black solid; dry the black solid in an oven overnight to obtain a modified P2 phase sodium manganese oxide material B.

[0037] (ii) An aqueous ammonium ion battery based on P2 sodium manganese oxide electrode material, the preparation method being:

[0038] The P2 sodium manganese oxide materials A and B obtained in Example 1 were used to prepare working electrodes, a platinum sheet was used as a counter electrode, and a saturated silver chloride electrode was used as a reference electrode. First, the working electrode, the counter electrode, and the reference electrode were screwed into the beaker device in sequence, the electrolyte was poured in, the beaker was screwed in, and the beaker was allowed to stand to obtain an aqueous ammonium ion battery based on the P2 phase sodium manganese oxide electrode material.

[0039] The preparation method is as follows:

[0040] (1) Preparation of working electrode: 80 mg of P2 sodium manganese oxide materials A and B obtained in Example 1, 10 mg of conductive agent SuperP and 10 mg of binder PVDF were added to a mortar, and a small amount of NMP solvent was added to allow the materials to fully contact. The slurry was ground for 30 minutes to obtain a uniformly ground slurry. The slurry was then directly and evenly coated on the carbon cloth. It was placed in a vacuum drying oven and dried at 60°C for 12 hours. The working electrode plates A and B coated with P2 sodium manganese oxide materials were obtained.

[0041] (2) Preparation of aqueous ammonium ion battery: Cut the working electrode carbon cloths A and B coated with P2 phase sodium manganese oxide material and clamp them into electrode clamps respectively, then screw the working electrode, counter electrode and reference electrode into the beaker device in turn, pour in 20 ml of 1M ammonium sulfate electrolyte, tighten and let stand to obtain an aqueous ammonium ion battery based on P2 phase sodium manganese oxide electrode material.

[0042] (3) The aqueous ammonium ion battery in (2) was subjected to electrochemical testing, with a voltage window of 0-1.2 V.

[0043] Example 2

[0044] P2 sodium manganese oxide material, the preparation method is as follows:

[0045] Weigh 0.74193g of sodium carbonate and 1.5787g of manganese trioxide in a mortar, mix them evenly and grind them for 30 minutes to obtain a black powder; evenly put the obtained black powder into a corundum porcelain boat, place it in a muffle furnace and calcine it at 900°C for 15 hours to obtain a P2 phase sodium manganese oxide material A; weigh 0.04g of tannic acid and dissolve it in 100ml of aqueous solution, mix it evenly and transfer it to a centrifuge tube, weigh 0.3g of P2 phase sodium manganese oxide material A and pour it into a centrifuge tube, mix it evenly, transfer it to an oven, 85°C for 15 minutes; centrifuge and wash it with alcohol 3 times to obtain a black solid; dry the black solid in an oven overnight to obtain a modified P2 phase sodium manganese oxide material B.

[0046] The preparation method and testing conditions of the aqueous ammonium ion battery of Example 2 are the same as those of Example 1.

[0047] Example 3

[0048] P2 sodium manganese oxide material, the preparation method is as follows:

[0049] Weigh 0.74193g of sodium carbonate and 1.5787g of manganese trioxide in a mortar, simply mix them evenly and grind them for 30 minutes to obtain a black powder; evenly put the obtained black powder into a corundum porcelain boat, place it in a muffle furnace and calcine it at 900°C for 15 hours to obtain a P2 phase sodium manganese oxide material A; weigh 0.08g of tannic acid and dissolve it in 100ml of aqueous solution, mix it evenly and transfer it to a centrifuge tube; weigh 0.3g of P2 phase sodium manganese oxide material A into a centrifuge tube, mix it evenly, transfer it to an oven, 85°C for 15 minutes; centrifuge and wash it with alcohol 3 times to obtain a black solid; dry the black solid in an oven overnight to obtain a modified P2 phase sodium manganese oxide material B.

[0050] The preparation method and testing conditions of the aqueous ammonium ion battery of Example 3 are the same as those of Example 1.

[0051] Figure 1 The EDS graphs of the P2 sodium manganese oxide material electrode material A prepared in Example 1 of the present invention and the P2 sodium manganese oxide electrode material B after being soaked in tannic acid are shown in FIG. Figure 1 It can be seen that the Mn content of the P2 sodium manganese oxide material was greatly reduced after being soaked in tannic acid, indicating that a certain amount of Mn dissolution occurred.

[0052] Figure 2 : is the XRD diagram of electrode material A, Example 1B, Example 2B, and Example 3B prepared by the present invention. Figure 2 It can be seen that by comparing with the card (PDF#00-027-0751), all diffraction peaks are consistent, proving that the synthesized material is P2 sodium manganese oxide Na 0.7 MnO 2.05 And by comparison, it can be seen that the immersion in tannic acid did not change the phase structure of the material, but the (002) crystal plane shifted to a certain extent, and the interlayer spacing increased.

[0053] Figure 3 : is the Laman diagram of electrode material A, Example 1B, Example 2B, and Example 3B prepared by the present invention. Figure 3 It can be seen that after being soaked in tannic acid, the Mn-O bond of the P2 sodium manganese oxide material shifts to the right, the bond length becomes shorter, and the bond strength becomes stronger.

[0054] Figure 4 The electrode materials A, Example 1B, Example 2B and Example 3B prepared by the present invention are used in aqueous ammonium ion batteries at 1.5 mVs -1 Cyclic voltammetry curve at scanning rate. Figure 4 It can be seen that the aqueous ammonium ion battery based on the sodium manganese oxide electrode material prepared in the embodiment has a cyclic voltammetry curve at 1.5 mV s -1The scanning speed showed a stable electrochemical window of 0-1.2 V, and the P2 phase sodium manganese oxide electrode material Example 2B showed a larger capacity after being soaked in tannic acid.

[0055] Figure 5 The electrode materials A, Example 1B, Example 2B and Example 3B prepared by the present invention are used in aqueous ammonium ion batteries at 0.5Ag -1 Capacity comparison chart at current density. Figure 5 It can be seen that the capacity of the aqueous ammonium ion battery based on the P2 phase sodium manganese oxide electrode material B soaked in tannic acid prepared in Example 2 can reach 196 mAh g -1 , showing good electrochemical performance.

[0056] Figure 6 The figure is a comparison chart of the rate of use of the electrode material A, Example 1B, Example 2B, and Example 3B prepared by the present invention in aqueous ammonium ion batteries at different current densities. Figure 6 It can be seen that the aqueous ammonium ion battery based on the P2 phase sodium manganese oxide electrode material B soaked in tannic acid prepared in Example 2 has a good rate capability and exhibits good electrochemical performance.

[0057] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a P2 phase sodium manganese oxide compound for aqueous ammonium ion batteries, characterized in that: The steps include: 1) Weighing sodium carbonate and manganese trioxide in a mortar, briefly mixing and evenly grinding for 30 minutes to obtain a black powder; evenly placing the obtained black powder into a corundum porcelain boat, placing it in a muffle furnace for calcination to obtain a P2 phase sodium manganese oxide material; 2) Weigh tannic acid and dissolve it in a beaker, mix well and transfer to a centrifuge tube; 3) Weigh the P2 phase sodium manganese oxide material synthesized in step 1) and pour it into the centrifuge tube in step 2), mix well, and transfer to an oven for heating; 4) centrifuging the centrifuge tube obtained in step 3) and washing with alcohol three times to obtain a black solid; 5) The black solid obtained in step 4) was placed in an oven and dried overnight to obtain the product.

2. The P2 phase sodium manganese oxide material according to claim 1, characterized in that: In step 1), the molar ratio of sodium carbonate to manganese trioxide is 0.5-0.

9.

3. The P2 phase sodium manganese oxide material according to claim 1, characterized in that: In step 1), the muffle furnace calcination conditions are: high temperature calcination at 500-900° C. for 10-15 hours.

4. The P2 phase sodium manganese oxide material according to claim 1, characterized in that: In step 2), the concentration of the tannic acid is: 0.02-0.08 g tannic acid is dissolved in 50-100 ml water.

5. The P2 phase sodium manganese oxide material according to claim 1, characterized in that: In step 2), the oven heating condition is: heating at 50-100° C. for 10-30 min.

6. Use of any one of the P2 phase sodium manganese oxide materials according to claims 1-5 as an electrode material in an aqueous ammonium ion battery.

7. The use according to claim 6, characterized in that: The method is as follows: P2 phase sodium manganese oxide material, polyvinylidene fluoride, superconducting carbon black and N-methylpyrrolidone are mixed, fully ground and evenly coated on the surface of the flexible carbon cloth current collector material to obtain a battery electrode.

8. The use according to claim 7, characterized in that: In terms of mass ratio, P2 phase sodium manganese oxide material: polyvinylidene fluoride: superconducting carbon = 8:1:1.